Reference gene selection for gene expression studies using RT-qPCR in virus-infected planthoppers - del Vas Mariana; Truol Graciela A; Mongelli Vanesa C; Sagadín Mónica; Maroniche Guillermo A (Virology Journal, 2011)
Abstract Background Planthoppers not only severely affect crops by causing mechanical damage when feeding but are also vectors of several plant virus species. The analysis of gene expression in persistently infected planthoppers might unveil the molecular basis of viral transmission. Quantitative real-time RT-PCR (RT-qPCR) is currently the most accurate and sensitive method used for quantitative gene expression analysis. In order to normalize the resulting quantitative data, reference genes with constant expression during the experimental procedures are needed. Results Partial sequences of the commonly used reference genes actin (ACT), α1-tubulin (TUB), glyceraldehyde 3-phosphate dehydrogenase (GAPDH), elongation factor 1 alpha (EF1A), ribosomal protein S18 (RPS18) and polyubiquitin C (UBI) from Delphacodes kuscheli, a planthopper capable of persistently transmitting the plant fijivirus Mal de Río Cuarto virus (MRCV), were isolated for the first time. Specific RT-qPCR primers were designed and the expression stability of these genes was assayed in MRCV-infective and naïve planthoppers using geNorm, Normfinder and BestKeeper tools. The overall analysis showed that UBI, followed by 18S and ACT, are the most suitable genes as internal controls for quantitative gene expression studies in MRCV-infective planthoppers, while TUB and EF1A are the most variable ones. Moreover, EF1A was upregulated by MRCV infection. Conclusions A RT-qPCR platform for gene expression analysis in the MRCV-infected planthopper vector Delphacodes kuscheli was developed. Our work is the first report on reference gene selection in virus-infected insects, and might serve as a precedent for future gene expression studies on MRCV and other virus-planthopper pathosystems.